An integrative review of project portfolio management ranking criteria - understanding better the decision-making process - Pionório Patrícia; Sebestyén Zoltán (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
Abstract. Project portfolio management (PPM) relies on rankings of projects, which can be challenging due to the many factors and people involved. Project prioritization is essential when a business works on multiple projects simultaneously (whether the projects are wholly independent or interdependent). Managing the projects already in the company’s portfolio and selecting new ones to add to the portfolio are among the essential tasks for many companies. The organization must prioritize the proper initiatives within its diversity to attain its goals and objectives. The ranking approach is a way to prioritize the projects by placing them in order from most important to least important by assigning each task a rating based on a set of criteria. These can be very diverse and depend on many factors, such as different financial and non-financial impacts). This study aims to provide a comprehensive assessment of the existing literature on studies in project portfolio management ranking, focusing on the ranking criteria employed and identifying the journals that published the papers we selected for this analysis. Before ranking, it is necessary to specify which criteria are most relevant to suit the organization’s goals. This research presents the main applicable criteria for ranking project portfolios and their sub-criteria to understand the potential of PPM better, leading to selecting more suitable and valuable projects for the organization. Based on this review, exploring the criteria used for the process, identifying the possibilities for their application, and gaining further knowledge of them enable better portfolio management for the company.

Резюме. Управління портфелем проектів (PPM) ґрунтується на рейтингах проектів, що може бути складним через багато факторів і залучених людей. Пріоритезація проектів є важливою, коли бізнес працює над декількома проектами одночасно, незалежно від того, чи є вони повністю незалежними чи взаємозалежними. Управління проектами, які вже є в портфоліо компанії, і вибір нових для додавання до портфоліо є одними з основних завдань для багатьох компаній. Організація повинна визначити пріоритетність відповідних ініціатив у своєму різноманітті для досягнення своїх цілей і завдань. Підхід до ранжування — це спосіб розставити проекти за пріоритетністю, розташувавши їх у порядку від найбільш важливого до найменш важливого, присвоївши кожному завданню рейтинг на основі набору критеріїв. Вони можуть бути дуже різними і залежати від багатьох факторів, таких як різні фінансові та нефінансові наслідки. Це дослідження має на меті забезпечити комплексну оцінку існуючої літератури щодо досліджень рейтингу управління портфелем проектів, зосередившись на використовуваних критеріях рейтингу та ідентифікації журналів, які опублікували статті, вибрані нами для цього аналізу. Перед ранжуванням необхідно визначити, які критерії найбільше відповідають цілям організації. У дослідженні представлено основні критерії та підкритерії, які використовуються для ранжування портфоліо проектів, щоб краще зрозуміти потенціал PPM для оптимального вибору більш прийнятних і цінних проектів для організації. Розуміння критеріїв, які використовуються для процесу, визначення можливостей їх застосування та отримання додаткових знань про них дозволяють компанії краще керувати портфелем проєктів.

Absztrakt. A projektportfólió-kezelés (PPM) projektminősítéseken alapul, amelyek a sok tényező és érintett személy miatt összetettek lehetnek. A projektek prioritása fontos, ha egy vállalkozás több projekten dolgozik egyidejűleg, függetlenül attól, hogy azok teljesen függetlenek vagy kölcsönösen függenek egymástól. A cég portfóliójában már meglévő projektek menedzselése és a portfólióba való újak kiválasztása sok vállalat fő feladatai közé tartozik. A szervezetnek a maga sokszínűségében meg kell határoznia a releváns kezdeményezések prioritását céljai és célkitűzései elérése érdekében. A rangsorolás a projektek rangsorolásának egyik módja a legfontosabbtól a legkevésbé fontosig történő elrendezéssel, és az egyes feladatokhoz egy kritériumrendszer alapján rangsorolnak. Ezek nagyon eltérőek lehetnek, és számos tényezőtől függhetnek, például különböző pénzügyi és nem pénzügyi tényzőktől. A tanulmány célja, hogy átfogó értékelést adjon a projektportfólió-menedzsment rangsorolási technika szakirodalomról, összpontosítva a használt rangsorolási kritériumokra, és azonosítva azokat a folyóiratokat, amelyek közzétették az elemzéshez kiválasztott cikkeket. A rangsorolás előtt meg kell határozni, hogy mely szempontok vonatkoznak leginkább a szervezet céljaira. A tanulmány bemutatja a projektportfólió rangsorolásához használt fő kritériumokat és alkritériumokat, hogy jobban megértsük a PPM-ben rejlő lehetőségeket a szervezet számára elfogadhatóbb és értékesebb projektek optimális kiválasztásában. A folyamathoz használt kritériumok megértése, alkalmazási lehetőségeinek meghatározása, azokkal kapcsolatos további ismeretek megszerzése lehetővé teszi a vállalat számára a projektportfólió jobb menedzselését.
Інтегративний огляд критеріїв ранжування управління портфелем проєктів для розуміння процесу прийняття рішень
A projektportfólió-kezelés rangsorolási kritériumainak integrált áttekintése a döntéshozatali folyamat megértéséhez
https://aab-economics.kmf.uz.ua/aabe/issue/view/3
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00012366
Keywords: project portfolio management; project portfolio ranking; ranking criteria